Hop-based Exclusive Neighborhood Caching Scheme for Content Centric IMANET - Kim, Backhyun; Kim, Iksoo; Woo, Yoseop (International Journal of Engineering and Technology, 2018)
MANETs have a relatively low transmission bandwidth and energy capacity, which is very different from a wired network. Frequent change of the transmission path due to movement of the node may cause problems such as service delay or disconnection in providing multimedia contents requiring transmission for a long time. A caching scheme that stores and uses the content being transmitted for future requests is an efficient technique in terms of use of transmission bandwidth and node energy. In this paper, caching is performed by selecting nodes that are not located within the transmission range of each other based on the hop distance among the nodes adjacent to the transmission path in the routing process. This can drastically reduce the number of neighboring nodes performing caching and decline the load on the node due to the low probability of being selected as a cache. Simulations were performed in terms of cache hit ratio, transmission channel reduction rate, and the number of caching nodes for various service request rates. From the simulation results, we can confirm that the proposed scheme adds a small number of caching nodes but substantially improves performance.Â Â